Cordillera in June essays celebrating June Prill-Brett, anthropologist - Tapang, Bienvenido P. (Quezon City University of the Philippines Press, 2007)
"This book of essays, Cordillera in June, is dedicated to June Prill-Brett, anthropologist. Every paper in the collection resonates with a theme that she has worked on as a scholar of the Cordillera. In her season of grace, we at UP Baguio celebrate June through this collection of articles contributed by her peers, colleagues, and one of her former students."--Preface.
Alterity and cultural existence / Julius D. Mendoza -- Feasts of merit : the politics of ethnography and ethnic icons in the Luzon highlands / Susan Russell -- "Tradition" as innovation, adaptation, and continuity among the Sagada Igorots of Northern Luzon as exemplified by the Dangtey ; notes on a ritual unique to Sagada Central / Villia Jefremovas -- Agricultural commercialization in Cordillera communities : a household perspective / Lorelei Crisologo Mendoza -- Searching for solutions : microfinance, poverty alleviation, and women's work in the Philippine Cordillera / B. Lynne Milgram -- Locality, place, and globalization on the Cordillera : building on the work of June Prill-Brett / Deirdre McKay -- Environmental stakes and legal pluralism in the Philippines and Indonesia / Padmapani L. Perez -- Simple but happy vs backward and miserable : representations of Vietnam's mountain minorities in Vietnamese newspapers / Dana Kim and A. Terry Rambo -- Power, property, and panarchy : opening the black box of cultural capital / Melanie G. Wiber.
Keywords: Cordillera Administrative Region (Philippines) -- Social conditions; Ethnology -- Philippines -- Cordillera Administrative Region; Cordillera Administrative Region (Philippines) -- Economic conditions